2021
DOI: 10.1177/10439862211001606
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Global Cyberterror Networks: An Empirical Study of Al-Qaeda and ISIS Cyberterrorism Events

Abstract: This study explores the internal dynamics and networks of terrorist groups in cyberspace—in particular, Al-Qaeda and the Islamic State of Iraq and al-Sham (ISIS). Using a “Global Cyberterrorism Dataset” that features data on cyberterror attacks between 2011 and 2016, this research analyzes these two terrorist groups through the lens of a cyber-conflict theory that integrates conflict theory with Jaishankar’s space transition theory. Through a network analysis methodology, we examine the invisible relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…This is further supported by cognitive inhibition effect in which, due to lack of deterrence, dissociation between the action and the end result encourages the continual terrorist behaviour [50]. Third, the ability to interchange between physical space and cyber space, alludes to the notion that terrorist activity may potentially manifest in cyber space where there are limited constraints to disseminate propaganda and recruit, prior to moving into physical space where offline impacts may be seen [52]. This available interchangeability is financially advantageous to terrorist groups as they can achieve their aims and objectives to further their terrorist ideology with reduced monetary costs.…”
Section: Space Transition Theorymentioning
confidence: 94%
See 1 more Smart Citation
“…This is further supported by cognitive inhibition effect in which, due to lack of deterrence, dissociation between the action and the end result encourages the continual terrorist behaviour [50]. Third, the ability to interchange between physical space and cyber space, alludes to the notion that terrorist activity may potentially manifest in cyber space where there are limited constraints to disseminate propaganda and recruit, prior to moving into physical space where offline impacts may be seen [52]. This available interchangeability is financially advantageous to terrorist groups as they can achieve their aims and objectives to further their terrorist ideology with reduced monetary costs.…”
Section: Space Transition Theorymentioning
confidence: 94%
“…Although this was an already advantageous aspect for terrorists, this has become even more significant due to the global COVID pandemic and lockdown restrictions [2]. Due to a greater increase in terrorist use of cyber space and its dynamic spatial -temporal characteristic, there is a lower risk of being caught due to the vastness of cyber environments [52]. Overall, the tenets highlighted in Space Transition Theory [14] simplify the advantageous elements which are enabling terrorist activity to continue mostly uninterrupted.…”
Section: Space Transition Theorymentioning
confidence: 99%
“…This Western-centric emphasis is explained by the disproportionately heavy reliance on digital systems that accompanies economic development, as well as the natural tendency to use terrorist tactics in asymmetric conflicts against more conventionally powerful states (Macdonald, Jarvis and Lavis 2019). We note, however, that new research has revealed that cyber terror attacks are increasingly targeting developing countries in the Middle East, Africa and South America as the threshold for obtaining destructive cyber tools becomes gradually lower (Lee et al forthcoming).…”
Section: A Three-country Survey Experimentsmentioning
confidence: 99%
“…The scope of the threat posed by this alarming new phenomenon, especially against critical infrastructure, was elucidated most prominently by former CIA Director and US Secretary of Defense Leon Panetta, when he insisted that the world was ‘facing the possibility of a ‘cyber-Pearl Harbor’ [that] could dismantle the nation's power grid, transportation system, financial networks and government’ (Bumiller and Shanker 2012). Even as skeptics question what is commonly viewed as a hyperbolic depiction of this threat (Lawson 2019; Gartzke 2013; Valeriano and Maness 2015), there is mounting evidence that terror organizations are adopting cyber tools to launch increasingly sophisticated attacks (Lee et al forthcoming), and significant cyber attacks on critical infrastructure have increased tenfold during the last decade (Noguchi and Ueda 2019). In the shadow of this debate, the public continues to exhibit mounting trepidation about the destructive capacity of cyber terrorism.…”
mentioning
confidence: 99%
“…Regardless of the drastic impacts of terrorism on business performance, research in the domain is scarce (Broeders et al, 2021;Shandler et al, 2022). More recently, scholars suggested examining the impact of terrorism on the financial performance of organizations (Lee et al, 2021;Okafor & Calderon, 2022).…”
mentioning
confidence: 99%